Analysis of the Density Variation on Thermal Conductivity Wood Plastic Composite Made from Lamtoro Wood (Leucaena leucocephala) And Polypropylene Waste - Hazlina Hazlina; Azrul Azwar; Asifa Asri (PRISMA FISIKA, 2022)
The thermal conductivity of Wood Plastic Composite (WPC) made with lamtoro wood and polypropylene (PP) was studied by varying its density. The PP was obtained from 240 ml mineral plastic glasses, and the lamtoro wood particles were shieved in 6 mesh sizes. In this study, we considered the composition ratio between PP and wood particles to be 70:30, and the thermal conductivity was measured using a thermal conductivity apparatus. Based on the data analysis, we found that the density of WPC made with PP and lamtoro wood influenced its thermal conductivity. The results showed that the thermal conductivity of sample A is 0.2 W/m ºC, sample B is 0.4 W/m ºC, and sample C is 0.5 W/m ºC, for the densities of 0.4 g/cm3, 0.5 g/cm3, 0.6 g/cm3, respectively. In conclusion, as the density increases, the thermal conductivity of WPC also increases. Thus, based on it thermal conductivity, the WPC made from PP and lamtoro wood is classified as an isolator.